2016
DOI: 10.3389/fpsyg.2016.01653
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Facial Signals on the Automatic Imitation of Hand Actions

Abstract: Imitation and facial signals are fundamental social cues that guide interactions with others, but little is known regarding the relationship between these behaviors. It is clear that during expression detection, we imitate observed expressions by engaging similar facial muscles. It is proposed that a cognitive system, which matches observed and performed actions, controls imitation and contributes to emotion understanding. However, there is little known regarding the consequences of recognizing affective state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 51 publications
3
18
1
Order By: Relevance
“…This could be interpreted as the consequence of the tendency of the subjects to accurately reciprocate to a social signal. In support of this hypothesis, our results on RTs are in line with previous studies showing a facilitation effect in performing congruent observed movements in response to emotional facial expressions (Rauchbauer et al, 2015 ; Butler et al, 2016 ); unfortunately, no parameters related to action execution were measured in those studies. However, an increase of accuracy requirements and motor control in response to emotional cues was found in previous experiments that measures kinematic parameters of goal-directed sequences addressed to a social partner (Ferri et al, 2010 ; Stefani et al, 2015 ), and in general during motor interactions in a positive social context (Gianelli et al, 2013 ), for a review see (Krishnan-Barman et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could be interpreted as the consequence of the tendency of the subjects to accurately reciprocate to a social signal. In support of this hypothesis, our results on RTs are in line with previous studies showing a facilitation effect in performing congruent observed movements in response to emotional facial expressions (Rauchbauer et al, 2015 ; Butler et al, 2016 ); unfortunately, no parameters related to action execution were measured in those studies. However, an increase of accuracy requirements and motor control in response to emotional cues was found in previous experiments that measures kinematic parameters of goal-directed sequences addressed to a social partner (Ferri et al, 2010 ; Stefani et al, 2015 ), and in general during motor interactions in a positive social context (Gianelli et al, 2013 ), for a review see (Krishnan-Barman et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Secondarily, faster movements in response to positive gestures confirmed that positive valence strongly modulates responses of the subjects during social interaction (Butler et al, 2016 ; De Stefani et al, 2016 ) Indeed, the shorter duration of lip-protrusion after observing a positive movement was measured in response to smile but not to anger; moreover, kiss resulted not effective as smile in speeding lip protrusion movements, evidencing a clear interaction between motor features and valence of the gesture. Instead, both negative and positive mouth-closure expressions, respectively kiss and spit, modulated the movement duration of lip stretching.…”
Section: Discussionmentioning
confidence: 61%
“…To this end, several recent studies have shown that social factors can influence SRC measures of imitation (Heyes, 2011;. SRC measures of imitation are increased in situations that promote affiliation through eye contact (Wang et al, 2011), group membership (Gleibs et al, 2016), and facial expressions (Butler et al, 2016), as well as when interacting with more human-like, rather than robotic, agents (Press, 2011;Kilner et al, 2003;Klapper et al, 2014). Other work has shown that when prosocial attitudes are generated (Cook & Bird, 2011;Leighton et al, 2010), or prosocial gestures are signalled , imitation increases.…”
Section: Convergent Validitymentioning
confidence: 99%
“…A number of previous studies have investigated the effect of different emotional expressions on the AI of finger movements ( Butler, Ward, & Ramsey, 2016 ; Crescentini, Mengotti, Grecucci, & Rumiati, 2011 ; Grecucci et al, 2013 ; Rauchbauer et al, 2015 , Rauchbauer et al, 2016 ). However, to date the results of these studies have been somewhat inconclusive.…”
Section: Introductionmentioning
confidence: 99%